Traditional Thai Community Conservation Focusing on Sustainable Participatory Process: A Case Study of Talaad Lang Community, Chumphon Province, Thailand - Chotewit Pongsermpol; Parinya Chukaew (My University, 2022)
We had investigated community conservation in actual practice and learnt that a sustainable and efficient approach to old community protection was a participatory conservation approach with cooperation from all stakeholders.This qualitative research aimed to express conservation principles for traditional communities and their implementation to the target community and to construct a guideline for sustainable community conservation in Thailand.We focused on a 'Talaad-Lang Community' group of buildings on Wanit Bamrung Road, Sawi District, Chumphon Province, and its surrounding area with around 100 years of history.In 2012-2014, we collected its historical, architectural, and socio-economic data from secondary sources, measurements, focus groups, exchange meetings, questionnaires, and interviews and followed up until 2020.The results of this study indicate how the community was able to implement its preservation practices that were both effective and sustainable.We arranged five main participatory processes: value identification, documentation, assessment, development, and implementation of sub-processes, such as arranging informational meeting, collecting data, setting up a coordinating group as well as creating a community image and tourism business.In conclusion, the participatory conservation approach was a significant and efficient method for old community conservation being to create community awareness, to support locally driven conservation efforts, and to help sustain the heritage community.
Keywords: Community Participation; Southeast Asian Sociopolitical Studies